(untitled) (Annals of Medical Research, 2021)
Aim: To evaluate the accuracy and agreement of the measurements made with the Masimo Rad7 device in living donor hepatectomy (LDH). Materials and Methods: A total of 63 living liver donors (LLDs) with ASA I-II scores who scheduled for LDH were included in the study. The Masimo noninvasive measurement probe was inserted to measure SpHb (mg/dL), pleth variability index (PVI, %) and perfusion index (PI,%). Heart rate, mean artery pressure, SpO2, body temperature, BIS, PVI, SpHb, and PI were recorded as basal, after anesthesia induction, post-intubation, post-intubation plus 5 min, 10 min, and plus 1, 2, 3, 4, 5, 6 and 7h. In addition blood samples were collected for laboratory hemoglobin (Hblab) before the surgery incision and after the surgical procedure, and the values were recorded simultaneously with the other values. Results: Fifty-five LLDs age between 18 and 55 years were assessed. The mean PI value increased in all measurements compared to baseline, and it was statistically significant at the 5th minute (p<0.05). This value prominently decreased after the 20th minute and dropped below the baseline value at the 7th hour. This decrease was statistically significant at the 2nd hour measurements (p<0.05). A significant correlation was observed between SpHb and LabHb before the surgical incision (r=0.694, p<0.001). Correlation decreased in after surgery measurement. In addition, there was a statistically significant difference between the before surgery and after surgery PI measurements (p<0.001). Conclusion: We think that in LDH procedures, surgical process leads to a decrease in PI and reduces the accuracy of SpHb measurement, and thus, intraoperative SpHb monitoring should be evaluated together with PI value.